Accessing the Nonlinear Regime with Selectively Laser Etched High-Q Microresonators - Bi, Toby; Beckmann, Lara; Thoms, Julian M.; Wenk, Max; Zhang, Shuangyou; Kratz, Martin; Del'haye, Pascal (16th Pacific Rim Conference on Lasers and Electro-Optics, CLEO-PR 2024, 2024)
Fused silica microresonators fabricated with the selective laser etching and annealing process with high-Q factors is presented. Due to the high-Q factors, frequency comb generation, stimulated Raman scattering, and opto-mechanical instability are experimentally observed.
CRIS-Team Scopus Importer:2024-10-25